Sustainability of Cultural Identity of Ex-Adherents Kawula Warga Naluri of 1966-1971 in Banjarnegara, Indonesia - Sulani, Puji; Wibowo, Priyanto; Muas, Tuty Nur Mutia Enoch (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2021)
This article describes the interaction between the structure and agency of ex-adherent of Kawula Warga Naluri in Banjarnegara District to maintain cultural identity and fight against the stereotype of